2023
DOI: 10.1021/acsami.2c16818
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Vacancy Abundant Nanoporous Ni/NiMnO3/MnO2@NiMn Electrodes with Ultrahigh Capacitance and Energy Density for Supercapacitors

Abstract: High-performance energy storage devices (HPEDs) play a critical role in the realization of clean energy and thus enable the overarching pursuit of nonpolluting, green technologies. Supercapacitors are one class of such lucrative HPEDs; however, a serious limiting factor of supercapacitor technology is its sub-par energy density. This report presents hitherto unchartered pathway of physical deformation, chemical dealloying, and microstructure engineering to produce ultrahigh-capacitance, energy-dense NiMn alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Ni 2 O 3 (Ni 3+ -855.9 ± 0.2 eV) was observed with shakeup satellite peak for both the specimen. The presence of metallic nickel was also found on the AsC specimen and additionally NiO (Ni 2+ -854.3 ± 0.2 eV) was observed in the AsC OP @5 specimen [25]. The Cu-2p spectra confirms the presence of CuO (Cu 2+ -933.5 ± 0.2 eV) and Cu 2 O (Cu + -932.5 ± 0.2 eV) for both the AsC and AsC OP @5 specimen [26,27].…”
Section: Structural and Morphological Characterizationmentioning
confidence: 78%
“…Ni 2 O 3 (Ni 3+ -855.9 ± 0.2 eV) was observed with shakeup satellite peak for both the specimen. The presence of metallic nickel was also found on the AsC specimen and additionally NiO (Ni 2+ -854.3 ± 0.2 eV) was observed in the AsC OP @5 specimen [25]. The Cu-2p spectra confirms the presence of CuO (Cu 2+ -933.5 ± 0.2 eV) and Cu 2 O (Cu + -932.5 ± 0.2 eV) for both the AsC and AsC OP @5 specimen [26,27].…”
Section: Structural and Morphological Characterizationmentioning
confidence: 78%
“…The water contact angle measurements for the aerogels, shown in Figure S9, confirmed their superhydrophilic nature, indicating excellent contact between the electrode and the electrolyte. This is crucial for good electrochemical performance as it minimizes the contact and charge transfer resistance . The nanoporous structure of the electrodes, as observed from the SEM images, ensures a small ion diffusion path.…”
Section: Resultsmentioning
confidence: 98%
“…This is crucial for good electrochemical performance as it minimizes the contact and charge transfer resistance. 75 The nanoporous structure of the electrodes, as observed from the SEM images, ensures a small ion diffusion path. The presence of CNTs enhances the electrical conductivity of the samples, thus providing them with excellent electrochemical performance.…”
Section: Ndmentioning
confidence: 95%
“…21 Some research studies and our previous studies have found that NiMnO-based electrodes derived from solid solution alloys could display this special electrochemical performance and facilitate the capacitance enhancement. [22][23][24] Nevertheless, just chemical synthesis or doping cannot achieve continuous redox reactions. 25,26 The reason why this kind of electrode can exhibit such a special electrochemical performance and its energy storage mechanism are still unknown.…”
Section: Introductionmentioning
confidence: 99%